VOC-Sensing Properties of Adsorption/Combustion-Type Micro Gas Sensors Using Mesoporous Alumina Co-Loaded with Pt and Metal Oxide. (16th August 2016) - Nagae, Kazunori; Ueda, Taro; Sasahara, Takahiko; Nakagoe, Osamu; Tanabe, Shuji; Hyodo, Takeo; Shimizu, Yasuhiro
Abstract : Mesoporous (mp-) Al2 O3 powders loaded with n wt% MO (Bi2 O3, CeO2, Fe2 O3, NiO, RuO2 or ZrO2 ( n = 1, 5, 10 )) and/or 1 wt% Pt nanoparticles ( 1.0 Pt/ n MO-mp-Al2 O3 ) were synthesized by an impregnation or a sonochemical reduction method. The sensor-signal profiles typically consist of one large dynamic response and subsequent static response, which originate from the flash catalytic combustion of these adsorbates and general catalytic combustion, respectively, during the pulse heating. The 1.0 Pt/ n CeO2 -mp-Al2 O3 sensor showed the largest static response to all target VOCs (ethanol, ethyl acetate, acetone, benzene and toluene), probably due to the largest specific surface area (ca. 187 m 2 g -1 ) among the sensors examined. In addition, the sensor also showed the largest dynamic response to most of target VOCs except for toluene. On the other hand, 1.0 Pt/ 10 Bi2 O3 -mp-Al2 O3 sensor showed the largest dynamic response to toluene and the dynamic response speed of the 1.0 Pt/ 10 Bi2 O3 -mp-Al2 O3 sensor to toluene was faster than that of the 1.0 Pt/ 10 CeO2 -mp-Al2 O3 sensor. This is probably because of more accelerated catalytic combustion behavior and the adsorption property of toluene over 1.0 Pt/ 10 Bi2 O3 -mp-Al2 O3 than those over 1.0 Pt/ 10 CeO2 -mp-Al2 O3 .